1998
DOI: 10.1161/01.res.82.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Hemodynamics in Endothelial NO Synthase Knockout Mice

Abstract: Abstract-For the specific analysis of endothelial NO synthase (eNOS) function in the coronary vasculature, we generated a mouse homozygous for a defective eNOS gene (eNOSϪ/Ϫ). Western blot as well as immunohistochemical staining revealed the absence of eNOS protein in eNOSϪ/Ϫ mice. Aortic endothelial cells derived from eNOSϪ/Ϫ mice displayed only background levels of NO x formation compared with wild-type (WT) cells (88 versus 1990 pmol). eNOSϪ/Ϫ mice were hypertensive (mean arterial pressure, 135Ϯ15 versus 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
182
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(202 citation statements)
references
References 41 publications
17
182
3
Order By: Relevance
“…Thus, in general, energy metabolism in the heart was preserved in both sedentary and active mice under conditions of eNOS knockout, so that the low physical activity of eNOSϪ/Ϫ animals did not result from altered cardiac energetics. In addition, eNOSϪ/Ϫ mice demonstrate no changes in basal coronary flow (15), and in basal conditions they have normal cardiac hemodynamics (56) as well as inotropic and lusitropic responses (11). Under conditions of ␤-adrenergic stimulation, eNOSϪ/Ϫ hearts even demonstrate augmented inotropy (2,35).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in general, energy metabolism in the heart was preserved in both sedentary and active mice under conditions of eNOS knockout, so that the low physical activity of eNOSϪ/Ϫ animals did not result from altered cardiac energetics. In addition, eNOSϪ/Ϫ mice demonstrate no changes in basal coronary flow (15), and in basal conditions they have normal cardiac hemodynamics (56) as well as inotropic and lusitropic responses (11). Under conditions of ␤-adrenergic stimulation, eNOSϪ/Ϫ hearts even demonstrate augmented inotropy (2,35).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that proangiogenic factors are upregulated and compensated for the loss of eNOS function and promote postnatal development of myocardial capillaries in those surviving eNOS Ϫ/Ϫ mice. Lack of eNOS may induce postnatally an increase in some angiogenic factors, such as angiotensin (22) and prostaglandins (13). Whether these factors are involved in the myocardial capillary development in adult eNOS Ϫ/Ϫ mice requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Chaitagneau et al 18 demonstrated that endothelium-dependent relaxations to ACh in aortae and left descending coronary arteries of C57BL/ 6J mice were completely abolished by inhibition of NOS or by gene-targeted deletion of eNOS (eNOSde®cient mice), indicating that in these vessels NO is the main contributor to the response to ACh. However, in contrast, in the integrated coronary bed Godecke et al 7,19 demonstrated that, whilst responses to bradykinin are predominantly NOmediated,19±20 responses to ACh have a signi®cant prostacyclin-dependent component. EDHF did not appear to contribute to coronary relaxation in response to these endothelium-dependent vasodilators.…”
Section: Discussionmentioning
confidence: 98%
“…During a 20-min equilibration period, coronary¯ow was adjusted to achieve a coronary perfusion pressure (CPP) of 60 AE 5 mmHg as used previously. 7 A CPP of 60 mmHg was found to produce optimal vasodilator responses and preliminary experiments demonstrated that left ventricular (LV) function was normal at this level. CPP was measured via a pressure transducer and data recorded on a MacLab/8 s system (ADI, Australia).…”
Section: Isolated Langendorff-perfused Heartsmentioning
confidence: 98%
See 1 more Smart Citation